Morphological characteristics of Cystoseira s. l. taxa of the flora of Ukraine - Sadogurska, S.S. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2023)
The article presents the results of morphological and anatomical analysis of the Cystoseira sensu lato taxa in the flora of Ukraine, taking into account modern views on the nomenclature of the genus. Earlier, based on the morphological and molecular phylogenetic analysis, it was shown that along the Ukrainian shores the polyphyletic genus Cystoseira s. l. is represented by three taxa (Ericaria crinita f. bosphorica (Sauvageau) S.S.Sadogurska, J.Neiva et A.Israel., Gongolaria barbata (Stackhouse) Kuntze f. barbata and Gongolaria barbata f. repens (A.D.Zinova & Kalugina) S.S.Sadogurska). As the result of the present study, for these taxa, a set of morphological features of vegetative and generative organs was analysed (general thallus appearance, structure of the apex and branches, presence/absence of appendages, aerocysts, shape and size of receptacles, presence/absence of iridescence, conceptacles, shape and structure of gametangia), as well as an analysis of the anatomical structure of the thallus (cortex and meristoderm cells on a cross section) was carried out. The analysis showed that these taxa have a wide range of morphological variability, which makes their identification difficult. At the same time, some characteristics are diagnostic and allow reliably distinguish and identify the studied taxa of the genus Cystoseira s. l. Based on the analysis, we provided a description of the main morphological and anatomical c haracteristics of the taxa and proposed identification keys for taxa of the genus Cystoseira s. l. of the flora of Ukraine. The results of the study of morphological features and the range of macroalgae morphological variability are important for further taxonomic studies, as well as clarification of keys for their identification.